Obstacles to the application of Total quality management in schools of general education "A field study in the city of Lattakia" - Tayyoub, Mahmoud; Darwiech, Ramadan; Hussein, Mahmoud Hasan (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن الوصول إلى نظام تعليمي متكامل ومتشبع بالجودة يتطلب تدريباً مكثفاً لكافة الأطراف التعليمية المشاركة في العملية التعليمية، من أجل بناء ثقافة تنظيمية جديدة تتبنى الجودة الشاملة فلسفةً جديدة للنهوض بمستواها وتحقيق الأهداف المنشودة. يتناول البحث الحالي معوقات تطبيق الجودة الشاملة في مدارس التعليم العام والمتمثلة بـ (معوقات تتعلق بالبيئة المدرسية, معوقات تتعلق بالإدارة المدرسية, معوقات تتعلق بالمعلم, معوقات تتعلق بالمتعلم, معوقات تتعلق بالمقررات الدراسية, معوقات تتعلق بعلاقة المدرسة بالمجتمع), ولتحقيق أهداف البحث تمّ تصميم استبانة وتوزيعها على عينة من مديري مدارس التعليم العام بمدينة اللاذقية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: - تواجه مدارس التعليم العام مجموعة من المعوقات التي تحول دون تطبيق الجودة الشاملة أهمها: عدم توفر ميزانية خاصة للمدرسة, عدم كفاية المكتبة المدرسية, وجود مقاومة للتغيير والتردد في تطبيق الجودة, ضعف التأهيل والتدريب ومهارات التواصل, عدم استخدام التقنيات الحديثة في التدريس, عدم قدرة المقررات الدراسية على استيعاب متغيرات العصر وضعف ارتباطها بحاجات المجتمع، وقلة التركيز على التطبيقات العملية, وضعف مشاركة القطاع الخاص في برامج المدرسة, ضعف علاقة المدرسة بالمجتمع المحلي. - عدم وجود فروق بين متوسطات إجابات أفراد العينة في المعوقات التي تحول دون تطبيق الجودة الشاملة تبعاً لمتغير نوع المدرسة. - وجود فروق بين متوسطات إجابات أفراد العينة في المعوقات التي تحول دون تطبيق الجودة الشاملة تبعاً لمتغيرات المؤهل العلمي وسنوات الخبرة والدورات التدريبية. Access to an integrated educational system and the saturated quality requires extensive training for all parties participating in the educational learning process for the construction of a new organizational culture to adopt a new philosophy of Total quality management quality for the advancement of their level and achieve the desired goals. The research deals with constraints to the application of total quality management in the schools of general education and with (constraints on the school environment, constraints related to management school, obstacles related to the teacher, constraints related to the learner, constraints on the decisions of study, constraints concerning the relationship of the school community), and to achieve objectives of the research, a questionnaire was designed and distributed to a sample of managers of public schools in the city of Lattakia. After the study and analysis, the researcher reached following results: - the public schools face a range of obstacles that prevent the application of TQM including: the lack of a special budget for the school, inadequate school library, the resistance to change and frequency in the application of quality, poor rehabilitation, training and communication skills, non-use of modern technologies in teaching, the inability of courses to accommodate the variables age and weakness linked to the needs of society and lack of focus on practical applications, the weakening of private sector participation in school programs, poor relationship with the school community. - The lack of differences between the averages of responses of respondents in the obstacles that prevent the application of total quality variable depending on the type of school. - The existence of differences between the averages of responses of respondents in the obstacles that prevent the application of total quality management due to the variables qualifications and years of experience and training courses.